2017
DOI: 10.5194/bg-2017-73
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrous oxide variability at sub-kilometre resolution in the Atlantic sector of the Southern Ocean

Abstract: The Southern Ocean is an important region for global nitrous oxide (N 2 O) cycling. The contribution of different source and 10 sink mechanisms is, however, not very well constrained due to a scarcity of seawater data from the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Therefore, a front may exist at this location. Butler et al (1989), Grefe et al (2018), and Rees et al (1997) also show that N 2 O saturation may be elevated or variable at fronts. Elevated saturation levels may result from the water mixing process at the frontal structure (Rees et al 1997), where a sharp change in temperature leads to a sharp change in gas solubility, or due to the presence of eddies (Rees et al 1997), which uplift N 2 O‐rich deeper water and lead to surface water N 2 O oversaturation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, a front may exist at this location. Butler et al (1989), Grefe et al (2018), and Rees et al (1997) also show that N 2 O saturation may be elevated or variable at fronts. Elevated saturation levels may result from the water mixing process at the frontal structure (Rees et al 1997), where a sharp change in temperature leads to a sharp change in gas solubility, or due to the presence of eddies (Rees et al 1997), which uplift N 2 O‐rich deeper water and lead to surface water N 2 O oversaturation.…”
Section: Resultsmentioning
confidence: 94%
“…However, although N 2 O production is less active in the open ocean than in the hotspots, the open ocean contributes significantly to the global budget (Dore et al 1998). Details on the N 2 O source and sink characteristics of hotspot regions, such as the Peruvian upwelling regions (Arévalo‐Martínez et al 2015), and the open ocean, such as the Southern Ocean (Grefe et al 2018), were further revealed with the development of high‐resolution underway observation systems based on off‐axis integrated cavity output spectroscopy (Arévalo‐Martínez et al 2013; Grefe and Kaiser 2014) and cavity ring down spectroscopy (Zhan et al 2018).…”
mentioning
confidence: 99%